Book Review - Succession Planning in Canadian Academic Libraries - Brunet, Mélanie (Université d'Ottawa | University of Ottawa, 2018)
Book review of Janneka Guise, Succession Planning in Canadian Academic Libraries. Waltham, MA: Chandos, 2016, 124pp.
Keywords: Succession planning; Academic libraries; Book review